Mechanical and thermal characterization of an epoxy foam as thermal layer insulation for a glass fiber reinforced polymer. Issue 47 (3rd September 2018) - Cavasin, M.; Giannis, S.; Salvo, M.; Casalegno, V.; Sangermano, M.
ABSTRACT: We have investigated the formulations and curing parameters to obtain an epoxy foam to be used as thermal insulator layer for a glass fiber reinforced polymer (GFRP). A relevant decrease (50%) of the apparent density of the foam was achieved by adding up to 5 wt % of foaming agent without affecting the glass‐transition temperature ( T g ). The mechanical properties were inevitably affected by the foaming, but a remarkable reduction down to 30% of the original value of the thermal conductivity was achieved. Morphological analysis by scanning electron microscopy showed a continuous interface between the epoxy GFRP and the foamed layer. © 2018 The Authors. Journal of Applied Polymer Science published by Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46864. Abstract :